Are Measurement Instruments Responsive to Assess Acute Responses to Load in High-Level Youth Soccer Players? - Ruf, Ludwig; Drust, Barry; Ehmann, Paul; Skorski, Sabrina; Meyer, Tim (Frontiers in Sports and Active Living, 2022)
Purpose: The aim of this study was to assess the short-term responsiveness of measurement instruments aiming at quantifying the acute psycho-physiological response to load in high-level adolescent soccer players. Methods: Data were collected from 16 high-level male youth soccer players from the Under 15 age group. Players were assessed on two occasions during the week: after two days of load accumulation ("high load") and after at least 48 hours of rest. Measurements consisted of the Short Recovery and Stress Scale (SRSS), a countermovement jump (CMJ) and a sub-maximal run to assess exercise heart-rate (HRex) and heart-rate recovery (HRR60s). Training load was quantified using total distance and high-speed running distance to express external and sRPE training load to express internal load. It was expected that good instruments can distinguish reliably between high load and rest. Results: Odd ratios (0.74 to 1.73) of rating one unit higher or lower were very low for athlete-reported ratings of stress and recovery of the SRSS. Standardized mean high load vs. rest differences for CMJ parameters were trivial to small (-0.31 to 0.34). The degree of evidence against the null hypothesis that changes are interchangeable ranged from p=0.04 to p=0.83. Moderate changes were observed for HRex (-0.62; 90%CL -0.78 to -0.47; p = 3.24 x 10-9), while small changes were evident for HRR60s (0.45; 90%CL 0.08 to 0.80; p = 0.04). Only small to moderate repeated-measures correlations were found between the accumulation of load and acute responses across all measurement instruments. The strongest relationships were observed between HRex and total distance (rm-r = -0.48; 90%CL -0.76 to -0.25). Conclusion: Results suggest that most of the investigated measurement instruments to assess acute psycho-physiological responses in adolescent soccer players have limited short-term responsiveness. This questions their potential usefulness to detect meaningful changes and manage subsequent training load and program adequate recovery.